Analisi Yuridis Pertanggungjawaban Pidana Kejahatan Terhadap Kemanusiaan Di Banten Dalam Perspektif UU HAM - Faturrohman Faturrohman; Analisa BR Gurusinga; Karina Agata Putri (Lembaga Pengembangan Kinerja Dosen, 2024)
Responsibility for human crimes is regulated in legislation, which is a very important topic in a country. Responsibility for a crime committed by humans includes several aspects, including an understanding of what is the basis of a crime, who is responsible for the crime, and how the legal system handles the violation.In many legal systems, liability for a crime usually includes three main elements: awareness (mens rea), action (actus reus), and the impact of the action. Awareness refers to the perpetrator's intention or knowledge when committing an act that is considered a crime. Action refers to a physical act or behavior that violates the law, while impact refers to the consequences of that action, either directly or indirectly.This legislation regulates various types of crimes and establishes sanctions or penalties for violations. These sanctions may vary depending on the severity of the crime, factors influencing the perpetrator, and other considerations. For example, minor crimes may only be punished by a fine or short prison sentence, while serious crimes can result in long-term prison sentences or even the death penalty in some jurisdictions.